PERIOPERATIVE ALGORITHM FOR REHABILITATION OF CHILDREN WITH ACUTE ENTERAL INSUFFICIENCY - A. A. Gumerov; A. N. Izosimov; V. V. Plechev; I. A. Mamleev; B. A. Oleinik (Креативная хирургия и онкология)
Application of the algorithm perioperative rehabilitation in acute  enteric disease in children  with  ksantinol-nikotinate test, where, thanks to the  introduction of  criteria  for  assessing  individual response of autonomic nervous  response of the  patient, as well as the correction of vascular therapy, it was passeble to more accurately affect the early recovery of peristalsis,  and in a timely manner be prevented formation of adhesions in the abdominal cavity, and the ways to manage contact electro-bowel in the postoperative period have developed, improve  outcomes, promote faster recovery  of  intestinal  motility and  reduce length  of  stay  in hospital. Intraoperative physiotherapy denervation diadynamic currents of sympathetic nerve fibers, going along the unpaired visceral branches of the abdominal aorta  can be clearly defined border  between viable and  pathologically altered  bowel  segment  during its necrosis,  as well as to avoid undue  over-resection of the colon healthy.